GAME ACTIVITIES IN THE TRAINING SYSTEM STUDENTS OF HIGHER PEDAGOGICAL INSTITUTIONS FOREIGN COMMUNICATION (Pedagogy of Higher and Secondary Education, 2004)
The article shows the essence of the students' playing activity during their foreign language communication training. The author gives the examples o f using some kinds of games in practice and demonstrates the effectiveness of using playing activities of students as prospective teachers in order to prepare them to foreign communication.